Inhibition of corrosion driven delamination on iron by smart-release bentonite cation-exchange pigments studied using a scanning Kelvin probe technique - Geraint Williams (6th International Conference: Advances in Corrosion Protection by Organic Coatings, 2017)
Low-cost, environmentally friendly, cation exchange pigments derived from naturally occurring bentonite clay are shown to significantly enhance resistance to corrosion-driven cathodic delamination in organic coatings adherent to iron surfaces. A scanning Kelvin probe (SKP) is used to study the delamination kinetics of pigmented and unpigmented poly-vinyl-butyral (PVB)-based coatings applied to polished iron substrates. The bentonite clay is used both in its native form and exhaustively exchanged with a range of divalent alkali earth and trivalent rare earth metal cations. For the best performing divalent cation-exchanged pigment, the dependence of coating delamination rate on pigment volume fraction is determined and compared with that of a conventional strontium chromate (SrCrO4) inhibitor. An inhibition mechanism is proposed for the bentonite pigments whereby underfilm cation release and subsequent precipitation of sparingly soluble hydroxides reduces the conductivity of the underfilm electrolyte.